2000
DOI: 10.1111/j.1745-9125.2000.tb00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and Fundamentalism: Reconsidering the Relationship Between Correctional Attitudes and Religion*

Abstract: Although research typically has failed to establish a relationship between religious affiliation and correctional attitudes, recent assessments have revealed that fundamentalist Christians tend to be more punitive than are nonfundamentalists. These studies have advanced our understanding considerably, but their conceptualization of religion and correctional attitudes has been limited. Using a statewide survey, the present study demonstrates that compassionate as well as fundamentalist aspects of religious beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
252
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(268 citation statements)
references
References 79 publications
10
252
2
4
Order By: Relevance
“…Applegate et al (2000) showed that when forgiving attitudes are measured beside punitive attitudes, the forgiving attitudes will prevail. Our study confirms this result in the sense that the factor analysis showed that rehabilitation-oriented attitudes explain more variance than punitive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Applegate et al (2000) showed that when forgiving attitudes are measured beside punitive attitudes, the forgiving attitudes will prevail. Our study confirms this result in the sense that the factor analysis showed that rehabilitation-oriented attitudes explain more variance than punitive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The GSS consisted of a full national probability sample . Some of the noted benefits of the 2004 survey were a larger sample size than previous surveys, more economic and racial diversity within the sample, and a wider variety of religious and spiritual measures Applegate, Cullen, Fisher, & Ven, 2000). In 2004, the final sample included 2,812 (1,280 men and 1,532 women) non-institutionalized English-speaking adults aged 18 years and older.…”
Section: Participantsmentioning
confidence: 99%
“…Importantly, it was the case for both first time and repeat offenders even when their gender was left unspecified, complementing the existing literature on the role of RWA (Altemeyer, 1996;Applegate et al 2000;Colémant, Van Hiel & Cornelis, 2011;Dunn, 2013;Feld, 2003;Funke, 2005;McKee & Feather, 2008;Tam, Leung and Chiu, 2008;Palasinski & Shortland, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…Christianity, for example, was found to be a positive correlate of support for corporal punishment and harsher laws (Applegate et al, 2000;Grasmick et al, 1992;Grasmick and McGill, 1994;Unnever et al, 2005;Unnever and Cullen, 2010). However, those viewing God as a guardian of justice were found to be more punitive than those viewing God as gracious and forgiving (Unnever et al, 2005).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation